(untitled) (Revista cientifica In Vestigium Ire, 2020)
This article on "Education for Sustainable Development: A strategy in intensive care", is a call for awareness of present and future generations, about the urgent need to reflect, do and think about how to work from different spaces and areas of performance to mitigate environmental damage to the environment where humanity lives and develops. From the particular vision of the authors, the real problems of the environment go beyond rationality, to the point of assuming that the strategy of environmental education has failed, since the environmental crisis is worrying because of its accelerated, massive and universal character, to which a region of the Colombian Amazon (Caquetá) is not alien. The general and specific bibliographic review of the department of Caquetá on the environment and environmental education for sustainable development reveals alteration of forests, extensive cattle raising, inadequate land management and different practices that show a relationship with poverty, malnutrition and food insecurity for a place like Caquetá with large extensions of land, good climate, water resources and extensive biodiversity. The results indicate a devastating social, environmental and economic context, which suggests that environmental education for sustainable development, several years after its implementation, is a strategy with minimal results in climate change, destruction of ecosystems, trafficking of species, among other socio‐environmental problems that in a consumerist globalization, are the elements of a pandemic cocktail for environmental education that is in intensive care because it has not worked as an effective treatment to the sensitivity of the plant.